INTEGRASI PENDIDIKAN AGAMA DENGAN ENTERREUNER DI LINGKUNGAN PONDOK PESANTREN (IMPLEMENTASI DI PONDOK PESANTREN ROUDHATUL IKHWAN KOTA TANGERANG SELATAN) - Budiman, Septian Arief; Rusli, Rahmatullah; Muhyi, Abdul; Mudzakir, Mudzakir; Ali, Fathudin (Universiitas Pamulang, 2021)
ABSTRACT The integration between religious education and entrepreneurship becomes an old concept that is renewed in the boarding school environment, the community's need for the world of work and an increase in the quality of output is very high, as one of the educational institutions in Indonesia has an obligation to innovate in order to realize these needs, one of the steps is implementing the program. enterpreuner based on religious education called the SANTRIPREUNER program. The community service team at Pamulang University in collaboration with the Roudhatul Ikhwan Islamic boarding school carried out community service activities for three consecutive days, from 11 to 13 December 2020 with the sharing session method and exposure to life skill management, while the target of this activity was the students. Roudhatul Ikhwan Islamic boarding school. The result of this activity was that the boarding schools were motivated again to implement the SANTRIPREUNER program that had been carried out, especially in the fields of agriculture and animal husbandry, the lecturers also found new formulas for the future in managing the program. Keywords: Santripreuner and Religious Education ABSTRAK Integrasi antara pendidikan agama dan enterpreuner menjadi konsep lama yang diperbarui di lingkungan pondok pesantren, kebutuhan masyarakat akan dunia kerja dan peningkatan kualitas output sangat tinggi, sebagai salah satu lembaga pendidikan di Indonesia memiliki kewajiban berinovasi dalam rangka mewujudkan kebutuhan tersebut, salah satu langkahnya ialah mengimplementasikan program enterpreuner berbasis pendidikan agama yang dinamakan program SANTRIPREUNER. Tim pengabdian kepada masyarakat Universitas Pamulang bekerjasama dengan pondok pesantren Roudhatul Ikhwan melaksanakan kegiatan pengabdian kepada masyarakat selama tiga hari berturut-turut yaitu tanggal 11 sampai dengan 13 desember 2020 dengan metode sharing session dan pemaparan tentang manajemen life skill, adapun sasaran pada kegiatan ini ialah para santri pondok pesantren Roudhatul Ikhwan. Hasil dari kegiatan ini ialah pihak pondok pesantren termotivasi kembali untuk melaksanakan program SANTRIPREUNER yang pernah dilakukan yaitu khususnya di bidang pertanian dan peternakan, para dosen juga menemukan rumusan baru untuk kedepannya dalam pengelolaan program tersebut. Kata Kunci: Santripreuner dan Pendidikan Agama